The tadpole of Afrixalus knysnae (Loveridge) (Anura: Hyperoliidae), with comments on reproductive biology - Lange, Ferdi De; Preez, Louis Du (Zootaxa, 2018)
Leaf–folding frogs of the genus Afrixalus comprise 33 species across South-East, Central and West Africa (Frost 2018) with tadpoles being described for Afrixalus aureus Pickersgill, A. delicatus Pickersgill, A. dorsalis (Peters), A. fornassinii (Bianconi), A. fulvovittatus (Cope), A. laevis (Ahl), A. morerei Dubois, A. nigeriensis Schiøtz, A. spinifrons (Cope), A. stuhlmanni (Pfeffer), A. uluguruensis (Barbour & Loveridge), A. vibekensis Schiøtz, A. vittiger Peters, and A. weidholzi (Mertens) (see Pickersgill 2005; Channing et al. 2012). Members of the genus have a unique approach to egg deposition, laying their eggs on soft-leaved hydrophytes. The male folds or rolls the leaf with his hind legs into a sheath following oviposition and fertilisation (Rose 1950; Wager 1954; Du Preez & Carruthers 2017), excreting an adhesive substance and enclosing the eggs within while the “glue” cures (Rose 1950, Wager 1954, authors pers. obs.).